Exacerbation of Inequities in Use of Diagnostic Radiology During the Early Stages of Reopening After COVID-19 - Lacson, Ronilda (J Am Coll Radiol, 2021)
OBJECTIVE: Assess diagnostic radiology examination utilization and associated social determinants of health during the early stages of reopening after state-mandated shutdown of nonurgent services because of coronavirus disease 2019 (COVID-19). METHODS: This institutional review board–approved, retrospective study assessed all patients with diagnostic radiology examinations performed at an academic medical center with eight affiliated outpatient facilities before (January 1, 2020, to March 8, 2020) and after (June 7, 2020, to July 15, 2020) the COVID-19 shutdown. Examinations during the shut down (March 9, 2020, to June 6, 2020) were excluded. Patient-specific factors (eg, race, ethnicity), imaging modalities, and care settings were extracted from the Research Data Warehouse. Primary outcome was the number of diagnostic radiology examinations per day compared pre- and post-COVID-19 shutdown. Univariate analysis and multivariable logistic regression determined features associated with completing an examination. RESULTS: Despite resumption of nonurgent services, marked decrease in radiology examination utilization persisted in all care settings post-COVID-19 shutdown (869 examinations per day preshutdown [59,080 examinations in 68 days] versus 502 examinations per day postshutdown [19,594 examinations in 39 days]), with more significantly decreased odds ratios for having examinations in inpatient and outpatient settings versus in the emergency department. Inequities worsened, with patients from communities with high rates of poverty, unemployment, and chronic disease having significantly lower odds of undergoing radiology examinations post-COVID-19 shutdown. Patients of Asian race and Hispanic ethnicity had significantly lower odds ratios for having examinations post-COVID-19 shutdown compared with White and non-Hispanic patients, respectively. DISCUSSION: The COVID-19 pandemic has exacerbated known pre-existing inequities in diagnostic radiology utilization. Resources should be allocated to address subgroups of patients who may be less likely to receive necessary diagnostic radiology examinations, potentially leading to compromised patient safety and quality of care.